2018
DOI: 10.1016/j.bios.2018.06.065
|View full text |Cite
|
Sign up to set email alerts
|

CLASP (Continuous lifestyle awareness through sweat platform): A novel sensor for simultaneous detection of alcohol and glucose from passive perspired sweat

Abstract: Wearable- IOT based low- cost platforms can enable dynamic lifestyle monitoring through enabling promising and exciting opportunities for wellness and chronic- disease management in personalized environments. Diabetic and pre- diabetic populations can modulate their alcohol intake by tracking their glycemic content continuously to prevent health risks through these platforms. We demonstrate the first technological proof of a combinatorial biosensor for continuous, dynamic monitoring of alcohol and glucose in u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 23 publications
(29 reference statements)
0
30
0
Order By: Relevance
“…Taking advantage of bioinformatics analysis, our results indicated that amino acid metabolism pathways, shared by the differentially expressed proteins and metabolites, were significantly altered in the VKH group. Although measurement of the sweat chloride concentration (sweat test) is the gold standard for the diagnosis of an immune disorder such as cystic fibrosis (CF) [22] and has also been proposed to monitor glucose in diabetic subjects [23], no other reports have been published so far, to our knowledge, concerning sweat composition in autoimmune disease. Earlier studies have reported the presence of proinflammatory molecules such as cytokines in sweat and showed a good correlation with plasma levels, suggesting that the analysis of sweat might form an alternative method to assess these factors in ambulatory settings where blood collection is difficult [24‐26].…”
Section: Discussionmentioning
confidence: 99%
“…Taking advantage of bioinformatics analysis, our results indicated that amino acid metabolism pathways, shared by the differentially expressed proteins and metabolites, were significantly altered in the VKH group. Although measurement of the sweat chloride concentration (sweat test) is the gold standard for the diagnosis of an immune disorder such as cystic fibrosis (CF) [22] and has also been proposed to monitor glucose in diabetic subjects [23], no other reports have been published so far, to our knowledge, concerning sweat composition in autoimmune disease. Earlier studies have reported the presence of proinflammatory molecules such as cytokines in sweat and showed a good correlation with plasma levels, suggesting that the analysis of sweat might form an alternative method to assess these factors in ambulatory settings where blood collection is difficult [24‐26].…”
Section: Discussionmentioning
confidence: 99%
“…Another factor to consider is that, although drop-out reasons have been described, the reasons for patients’ dropout were not clearly registered, which also hinders the interpretation of effectiveness data. Our results suggest that a shift in the implementation direction of digital interventions should be considered, and new approaches to digital interventions should exploit the potential of wearables ( Bhide et al, 2018 ; Dougherty et al, 2014 ; Mohan et al, 2017 ), multiplatform solutions and gamification to increase adherence ( Boyle et al, 2017 ). We hope that our report will improve future studies on digital interventions in this and other settings.…”
Section: Discussionmentioning
confidence: 98%
“…This device is not yet wearable, but when tested in real human sweat, it shows great potential in the application towards perspiration-based glucose sensing. This next study takes a non-invasive wearable approach to perspiration-based glucose monitoring ( Bhide et al, 2018 ). It makes use of ultra-low volumes of sweat for rapid and dynamic glucose monitoring, which can be applied to a wearable device in future.…”
Section: Continuous Monitoring Of Glucose In Different Body Fluidsmentioning
confidence: 99%